2017
DOI: 10.3389/fphar.2017.00722
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacist–Psychiatrist Collaborative Patient Education on Medication Adherence and Quality of Life (QOL) of Bipolar Affective Disorder (BPAD) Patients

Abstract: Background: Bipolar Affective Disorder (BPAD) is one of the leading causes of disability globally. Medication non-adherence and low quality of life (QOL) are the major challenges associated with the treatment of BPAD patients.Objective: Aim of this study was to assess the impact of pharmacist–psychiatrist collaborative patient education on medication adherence and QOL of BPAD patients.Methodology: A prospective randomized control study was conducted in the psychiatry outpatient department in a tertiary care se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…These interventions were delivered by the pharmacist individually or as a group and focused on medication and disease state information and lifestyle modification recommendations, discussing the importance of medication adherence, and providing advice on how to manage medication side effects. Educational and counselling materials were developed based on published information such as consumer information leaflets (Mishra et al, 2017a(Mishra et al, , 2017b or information derived from the US pharmacopoeia (Kaukab et al, 2015) or guidelines from the American Society of Hospital Pharmacists (Greco, 1994).…”
Section: Pharmacist-led Intervention Componentsmentioning
confidence: 99%
“…These interventions were delivered by the pharmacist individually or as a group and focused on medication and disease state information and lifestyle modification recommendations, discussing the importance of medication adherence, and providing advice on how to manage medication side effects. Educational and counselling materials were developed based on published information such as consumer information leaflets (Mishra et al, 2017a(Mishra et al, , 2017b or information derived from the US pharmacopoeia (Kaukab et al, 2015) or guidelines from the American Society of Hospital Pharmacists (Greco, 1994).…”
Section: Pharmacist-led Intervention Componentsmentioning
confidence: 99%
“…Pharmacists, as part of an interdisciplinary team, can have a number of clinical responsibilities and positive impact. These responsibilities may include providing medication information and recommendations to providers, [6][7][8] educating patients about psychotropic medications, 7,9 or providing direct patient care through office or telephone visits. 7,8,10,11 Outpatient psychiatric pharmacist services have made a significant impact on patient care.…”
Section: Introductionmentioning
confidence: 99%
“…These centers were established to provide psychosocial support services for patients with severe mental illness such as bipolar disorder, schizophrenia, and unspecified schizophrenia spectrum and other psychotic disorder (USS&OPD). Treatment adherence, quality of life and social cognitive functions are impaired in schizophrenia and bipolar disorder (6,7). Therefore, an integrated and multidimensional approach should be used to reduce non-adherence to treatment and increase the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…After patients are admitted to CMHC, psychotherapy is given to them, and patients along with their relatives are provided with psychoeducation and skill training by teachers assigned by public education centers, taking their needs and capabilities into consideration within the scope of orientation studies. The studies about participation frequencies were mostly on psycho-education frequency, antistigmatization and public awareness (7,9,10). A study found that psychosocial skills training once in two weeks was provided significant contribution in symptoms and functioning in nineteen schizophrenia patients (11).…”
Section: Introductionmentioning
confidence: 99%